2013
DOI: 10.1097/01.id.0000434273.22605.78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hierarchical Micro/Nano-Textured Titanium Surface Features on Osteoblast-Specific Gene Expression

Abstract: Hierarchical hybrid micro-/nanostructured titanium surface has a favorable biocompatibility, which can promote osteoblast differentiation. It could possibly accelerate bone growth, promote bone formation at early stage, and guarantee the immediate loading and early stage loading in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Nine studies found that specific surfaces induced osteoblast differentiation, expression of osteogenic genes or repression of the miRNAs that downregulate osteogenic genes [46][47][48]50,52,53,[58][59][60], while six articles did not indicate a better surface [49,51,[54][55][56][57]. Two articles documented similar trends in gene expression regardless of implant surface and found that the effect of time influenced gene expression more than the surfaces [49,54].…”
Section: Comparative Analysismentioning
confidence: 89%
See 4 more Smart Citations
“…Nine studies found that specific surfaces induced osteoblast differentiation, expression of osteogenic genes or repression of the miRNAs that downregulate osteogenic genes [46][47][48]50,52,53,[58][59][60], while six articles did not indicate a better surface [49,51,[54][55][56][57]. Two articles documented similar trends in gene expression regardless of implant surface and found that the effect of time influenced gene expression more than the surfaces [49,54].…”
Section: Comparative Analysismentioning
confidence: 89%
“…Publication types of the included articles are expressed in Figure 2. Fifteen of 17 articles were in vitro or in vivo studies [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. One was a randomized clinical trial with immune-histochemical analysis [61], and the other was a narrative review [62].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations